Case Report: Coinheritance of Germline Mutations in APC and BRCA1 in Colorectal Cancer - Huang, Wei; Bian, Jin; Qian, Xiaoping; Shao, Lin; Li, Haiyan; Zhang, Lu; Wang, Lin (Frontiers in Oncology, 2021)
Deleterious mutations in APC gene cause the autosomal dominant familial adenomatous polyposis (FAP) which is typically characterized by the occurrence of hundreds to thousands of colorectal adenomas that eventually lead to colorectal cancers (CRCs). BRCA1/2 are the two major susceptibility genes for breast and ovarian cancers. Here, we reported a coinheritance of mutations in APC and BRCA1 genes in a 20-year-old CRC patient with typical clinical features for FAP. Multiple relatives in the family of the patient were affected by colorectal and other cancers. Next-generation sequencing analysis using a panel consisting of 53 hereditary cancer related genes revealed a maternally inherited APC (exon15cn_del) mutation and a paternally inherited BRAC1 (p.lle1824AspfsX3) mutation. This is the first coexistence of APC and BRCA1 mutations in a CRC patient with the mutation inheritance pattern comprehensively characterized in the family. The patient underwent a colonoscopy and a subtotal colectomy and was subsequently diagnosed with colonic adenocarcinomas accompanied with hundreds of tubulovillous adenomas. The case reveals the scenario where two disease-causing mutations of different hereditary tumor syndromes coexist, and illustrates the importance of evaluating detailed family history and performing a multiple-gene panel test in patients with hereditary cancer.